The Effects of Brand Image, Product Quality, and Service Quality on Purchase Decisions at Calf Signature Arjuno, Malang - Nadya Putri Hariyoko; Rifki Hanif; Lussia Mariesti Andriany (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid expansion of the food and beverage industry, particularly the coffee shop sector, has intensified competition and increased the importance of understanding the factors that shape consumer purchase decisions. In this context, brand image, product quality, and service quality represent key strategic attributes that may influence consumer preferences and purchasing behavior. This study aims to examine the partial and simultaneous effects of brand image, product quality, and service quality on consumer purchase decisions at Calf Signature Arjuno Malang. A quantitative approach with a survey method was employed, and data were collected through questionnaires distributed to consumers. The collected data were analyzed using multiple linear regression with SPSS software. The findings indicate that brand image, product quality, and service quality positively influence consumer purchase decisions. Simultaneously, the three variables have a significant effect on purchase decisions, demonstrating their combined importance in shaping consumer behavior. These findings suggest that competitive performance in the coffee shop industry depends not only on product offerings but also on the strength of brand perceptions and the quality of customer service. This study contributes empirical evidence on the determinants of consumer purchase decisions in the coffee shop context and provides practical implications for business operators seeking to strengthen competitiveness. Accordingly, Calf Signature Arjuno Malang should continuously reinforce its brand image, maintain consistent product quality, and improve service quality to encourage consumer purchase decisions and sustain its competitive position. Keywords: Brand Image; Coffee Shop; Product Quality; Purchase Decision; Service Quality